2016
DOI: 10.1097/qad.0000000000001245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV-infection and cumulative viral load on age-related decline in grip strength

Abstract: Objective Grip strength predicts functional decline and death, and is regarded as a biomarker of biological aging. The primary objective of this manuscript was to assess differences in the rate of decline in grip strength in persons aging with and without HIV. Design Grip strength was assessed in 1,552 (716 HIV+ and 836 HIV−) men ≥ 50 years participating in the Multicenter AIDS Cohort Study between 2007 and 2014. Methods Grip strength decline was modeled longitudinally, adjusting for serostatus, demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 25 publications
3
52
1
1
Order By: Relevance
“…Both ART and HIV were found to have toxic effects on the muscle, with many of the older nucleoside reverse transcriptase inhibitor (NRTI) therapies later implicated in mitochondrial toxicity . HIV‐infected adults also have been shown to have gene expression patterns consistent with fibrosis and collagen deposition and to have greater fatty infiltration of the muscle and decreased strength with aging compared with HIV‐uninfected controls …”
Section: From Wasting To Obesity: Hiv and Its Therapy In Agingmentioning
confidence: 99%
“…Both ART and HIV were found to have toxic effects on the muscle, with many of the older nucleoside reverse transcriptase inhibitor (NRTI) therapies later implicated in mitochondrial toxicity . HIV‐infected adults also have been shown to have gene expression patterns consistent with fibrosis and collagen deposition and to have greater fatty infiltration of the muscle and decreased strength with aging compared with HIV‐uninfected controls …”
Section: From Wasting To Obesity: Hiv and Its Therapy In Agingmentioning
confidence: 99%
“…However, HIV-positive men had a more rapid decline in grip strength and clinical weakness occurred earlier. Factors contributing to frailty in HIV may include older age, lower BMI, diabetes mellitus, chronic kidney disease, peripheral neuropathy, and higher cumulative HIV viral load correlated with a greater longitudinal decline in grip strength [54]. …”
Section: Hiv: More Comorbidities and More Frailty But Frailty Assessmentioning
confidence: 99%
“…In the French Agency for AIDS and Hepatitis Research (ANRS) CO3 Aquitaine Cohort (n=324), 53% of subjects performed poorly in the five-times sit-to-stand test (5STS), a test of lower limb muscle performance [37] ; a longer duration of HIV diagnosis, but not of use of cART, was associated with poorer performance on the 5STS. Recent findings in the Multicenter AIDS Cohort Study (MACS) have suggested that both strength and gait speed decline faster after age 50 to 60 among HIV-infected compared to HIV- uninfected men, adjusted for viral suppression and other HIV-related factors, indicating an accelerated functional decline even with treated HIV infection [38, 39] . Importantly, loss of muscle strength and function is a major component of frailty, and is typically clinically apparent before loss of muscle mass [17] .…”
Section: Sarcopeniamentioning
confidence: 99%